Atrial Fibrillation is Associated with Femoropopliteal Totally Occlusive In-Stent Restenosis: A Single-Center, Retrospective, Observational Study. (3rd February 2021) - Honda, Yohsuke; Hirano, Keisuke; Yamawaki, Masahiro; Araki, Motoharu; Kobayashi, Norihiro; Sakamoto, Yasunari; Mori, Shinsuke; Tsutsumi, Masakazu; Makino, Kenji; Shirai, Shigemitsu; Mizusawa, Masafumi; Nakano, Takahiro; et al.
Abstract : Introduction . The proportion of patients with comorbid atrial fibrillation (AF) and peripheral artery disease (PAD) has increased in this era. This study aimed to assess the relationship between AF and totally occlusive in-stent restenosis (ISR) in femoropopliteal (FP) lesions. Methods . In this study, 363 patients (461 stents) who underwent endovascular therapy with de novo stent implantation in our hospital between April 2007 and December 2016 were retrospectively evaluated. The patients were divided into two groups according to the AF status (AF group, 61 patients; sinus group, 302 patients). The primary endpoint was the incidence of totally occlusive ISR within 3 years. The secondary endpoint was the incidence of acute limb ischemia (ALI) due to FP stent occlusion. Results . Baseline characteristics were similar, except for higher age and a lower prevalence of dyslipidemia in the AF group. The incidence of a totally occlusive ISR was higher in the AF group than in the sinus group (29.5% vs. 14.6%, p = 0.004 ). A multiple Cox regression model suggested that presence of AF (hazard ratio, 2.10) and CTO lesion (hazard ratio, 1.97) which were the independent predictors of a totally occlusive ISR within 3 years. The incidence of ALI was significantly higher in the AF group than in the sinus group (3.9% vs. 0%, p = 0.0001 ). In the AF group, the introduction of an anticoagulant did not prevent the occurrence of totally occlusive ISR (p = 0.71 ) for ALI (p = 0.79 ). Conclusions . AF is independently associated with totally occlusive ISR of FP stents; however, anticoagulant use does not prevent stent occlusion.